The improvement of cattle in British colonial territories in Africa - Faulkner, D.E.; Brown, J.D. (1953)
The monograph reports activities related to cattle improvement in the British colonial territories in Africa. It consists of four parts. Part one presents the general background to the improvement of cattle in the territories describing ecological conditions, economic and social significance of cattle, environmental and animal husbandry conditions. Part two follows with discussions on methods adopted by colonial governments for the improvement of cattle. This part outlines the objectives of cattle improvement programmes; methods of improvement involving selection of indigenous stock and introduction of exotic breeds; adaptability of the indigenous breeds to various environmental conditions and the government stock farms and improvement centres. Part three details some general principles of cattle improvement in tropical Africa focusing on grading-up processes and their applicability in the field. Part four presents specific problems of cattle improvement in each of the colonial territories. There are pictographic illustrations throughout the book, appendices and bibliography at the end.